Wettability of graphene by molten polymers. (10th October 2019) - Pastore Carbone, Maria Giovanna; Tammaro, Daniele; Manikas, Anastasios C.; Paterakis, George; Di Maio, Ernesto; Galiotis, Costas
Abstract: Graphene wetting by polymers is a critical issue to both the success of polymer-aided transfer of large size sheets onto specific substrates and to the development of well performing nanocomposites. Here we show for the first time that high temperature contact angle measurements can be performed to investigate the wettability of CVD graphene by molten polymers. In particular, poly(methyl methacrylate), a widely used polymer support for CVD graphene transfer, has been adopted herein for this proof-of-concept study and the values of contact angle and work of adhesion have been provided in the temperature range 170–200 °C. Graphical abstract: Image 1 Highlights: We show that high temperature contact angle measurements can be performed to investigate the wettability of CVD graphene by molten polymers. As proof-of-concept, the system molten PMMA on CVD graphene has been investigated in the temperature range 170 – 200 ° C. Kinetics of wetting were studied and the duration of the transient is consistent with the characteristic time for interfacial-tension-driven motions. The work of adhesion between graphene and PMMA has been calculated in the investigated temperature range.